Elaboration of nitride thin films by reactive sputtering - Jouan,Pierre Yves (2006)
The aim of this paper is first a better understanding of DC reactive magnetron sputtering and its implications, such as the hysteresis effect and the process instability. In a second part, this article is devoted to an example of specific application: Aluminium Nitride. AlN thin films have been deposited by reactive triode sputtering. We have studied the effect of the nitrogen contents in the discharge and the RF bias voltage on the growth of AlN films on Si(100) deposited by triode sputtering. Stoichiometry and crystal orientation of AlN films have been characterized by means of Fourier-transform infrared spectroscopy, X-ray diffraction and secondary electron microscopy. Dense and transparent AlN layers were obtained at high deposition rates. These films have a (002) orientation whatever the nitrogen content in the discharge, but the best crystallised ones are obtained at low value (10%). A linear relationship was observed between the AlN lattice parameter "c" (perpendicular to the substrate surface) and the in-plane compressive stress. Applying an RF bias to the substrate leads to a (100) texture, and films become amorphous. Moreover, the film's compressive stress increases up to a value of 8GPa before decreasing slowly as the bias voltage increases.